Performa Thin-Thick Orifice Plate Terhadap Kerugian Energi - Mahmuddin Mahmuddin; Muhammad Syahrir; Muhammad Imam Arif; Afryanto Pakambanan (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2025)
The measurement of the volumetric flow rate of fluids in a pipe is essential in process industries, particularly those utilizing pipelines as fluid transport media. Such process variable measurement is conducted to control the system according to a setpoint to achieve process optimization. An orifice plate meter is a type of flow meter used to measure the volumetric flow rate of fluids flowing inside a pipe based on the principle of differential pressure. The performance of an orifice plate meter can be determined by measuring the pressure at the upstream and downstream regions using pressure tappings connected to a manometer tube. The experimental observation of orifice performance was carried out by testing the orifice plate meter at ratios of (s/d) = 0.42, 0.83, and 1.25 with a restriction ratio (β) = 0.5. Pressure measurements at upstream and downstream regions were performed within the Reynolds number range of 6600–16500.The pressure distribution, discharge coefficient (Cd), and permanent pressure loss were considered as the main parameters in classifying the accuracy level of the orifice plate meter as a volumetric flow measurement device. The percentage of permanent pressure loss, referenced to centerline pressure at (s/d) = 0.42, 0.83, and 1.25, was found to be 49.87%, 54.37%, and 67.27%, respectively. The average discharge coefficient (Cd) at (s/d) = 0.83, with references to centerline pressure and D;0.5D, was 0.66 and 0.76, respectively, while for (s/d) = 1.25 the values were 0.65 and 0.68. Meanwhile, for (s/d) = 0.42, the average Cd obtained was 0.73, which is close to the analytical value given in ISO 5167-2 (2013).